ETIKA SOSIAL PERSPEKTIF MUFASSIR NUSANTARA: KAJIAN QS. AL-HUJURAT AYAT 9-13 DALAM TAFSIR AL-IBRIZ - Lukman Nul Hakim; Iffatul Bayyinah (CV. Doki Course and Training, 2023)
This article aims to find out the teachings of the Koran in terms of social ethics in QS. al-Hujurat verses 9-13 in the perspective of Tafsir Al-Ibriz by Indonesian scholars, KH. Bisri Musthofa. This is motivated by the fact that the development of the times with technological advances has had a significant impact on moral decadence. Therefore, it is important to know what forms of social ethics are contained in QS. al-Hujurat verses 9-13 on Tafsir Al-Ibriz. By using the descriptive-analytic method, it can be concluded that there are five forms of social ethics in the five verses (9-13) of surah al-Hujurat which play a very important role in social life, namely: first, being fair (verse 9), second, being conflict resolution (verse 10), the third, respects each other (verse 11), the fourth, is open (verse 12) and the fifth, respects differences. These five ethical values play an important role in the realization of peace in social life.